2018
DOI: 10.5582/bst.2018.01052
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA Linc00312 modulates the sensitivity of ovarian cancer to cisplatin <i>via</i> the Bcl-2/Caspase-3 signaling pathway

Abstract: Chemotherapy is one of the main treatments for ovarian cancer (OC). Cisplatin combined with paclitaxel is a commonly used chemotherapy regimen. However, effective cancer therapy is hindered by a patient's resistance to cisplatin. The mechanism that potentially leads to that resistance is unclear. The current study examined the mechanism by which Linc00312 is involved in resistance to cisplatin in OC. Quantitative real-time PCR (RT-qPCR) was used to test for expression of Linc00312 in freshly frozen tissue samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
1
22
1
Order By: Relevance
“…For example, Long et al confirmed that lncRNA GAS5 increased DDP-resistance and promoted OC cell growth through modulating MAPK pathway. 25 Miao et al reported that lncRNA ANRIL changed the sensitivity of OC cells to DDP by mediating let-7a and HMGA2 levels. 26 LncRNA linc00312 regulated DDP resistance of OC cells via modulating Bcl-2/Caspase-3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Long et al confirmed that lncRNA GAS5 increased DDP-resistance and promoted OC cell growth through modulating MAPK pathway. 25 Miao et al reported that lncRNA ANRIL changed the sensitivity of OC cells to DDP by mediating let-7a and HMGA2 levels. 26 LncRNA linc00312 regulated DDP resistance of OC cells via modulating Bcl-2/Caspase-3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (24) demonstrated that the downregulation of Hox transcript antisense intergenic RNA significantly decreased the levels of cell proliferation and invasion, and reversed cisplatin resistance in SKOV-3CDDP/R cells. In addition, Zhang et al (25) indicated that Linc00312 promoted apoptosis and enhanced cisplatin sensitivity through the Bcl-2/Caspase-3 pathway in SKOV3/DDP cells. These studies indicated that lncRNAs have great potential in the treatment of cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Various lncRNAs regulate the emergence of chemoresistance via modulating apoptosis. For instance, LINC00312 was shown to counteract PTX resistance in OC and enhance apoptosis via blocking BCL-2 and activating the Bax/Caspas3 apoptotic pathway [ 140 ]. Another lncRNA, CDKN2B-AS, also called antisense ncRNA in the INK4 locus (ANRIL), is overexpressed in a wide array of solid tumors such as hepatocellular carcinoma [ 153 ] and cervical [ 154 ], breast [ 155 ], endometrial, and prostate cancers [ 156 ].…”
Section: Lncrnas and Chemoresistance In Ovarian Cancermentioning
confidence: 99%